Javanese Language Shift to Indonesian Among Young People in Sleman, Yogyakarta - Noveintine, Dhanesvar Karel (CV. Ulil Albab Corp, 2025)
This study aims to explore the shift from Javanese to Indonesian among young people in Sleman, Yogyakarta. It focuses on how this language shift affects their Javanese proficiency and the phonological variations. The research shows that many young people prefer using Indonesian in their daily lives because of education, social media, and globalization influences. As a result, their Javanese skills are declining leading to a decrease in mastering vocabulary and pronunciation. The study uses interviews and observation methods to gather data from 15-20 participants aged 16 to 26 who are Javanese and live in Sleman. Participants were asked several questions in both Indonesian and Javanese languages and tested on their pronunciation of 8 pairs of homographs to find phonological variations. The findings show that young people often struggle with Javanese, especially Krama, and prefer Indonesian. This shift affects not only language use but also cultural identity and heritage. The study also elaborates on the factors that cause language shifts